Bagaimana net profit margin, total assets turnover, dan debt to equity ratio mempengaruhi earning per share pada perusahaan jakarta islamic indeks 70 - Marcelina, Gita Vegi; Setiawan, Ari (Journal of Accounting and Digital Finance, 2022)
This study aims to determine the effect of NPM, TATO, and DER on Earning Per Share both partially and simultaneously in Jakarta Islamic Index 70 (JII70) companies for the 2018-2020 period. The data used in this study is secondary data, namely the company's financial reports published by OJK. The number of samples used in this study was 41 samples of companies registered with the Jakarta Islamic Index 70 in the 2018-2020 period, which were taken using the purposive sampling method. The analytical method of this study uses panel data regression analysis. The results of this study indicate that the NPM and TATO variables significantly affect Earning Persahre. The DER variable has no significant effect on Earning Pershare, but simultaneously the independent variable has a significant effect on Earning Pershare.